Building a recommendation system with Surprise and Fast.ai. (Manning Publications, 2021)
Ariel Gamino shows how to put collaborative filtering techniques into action to create recommendation engines, one of the most useful types of machine learning application. You'll become familiar with the workflow of a professional data scientist.